Microwave and hydrothermal syntheses of WSe2 micro/nanorods and their application in supercapacitors - Chakravarty, Disha; Late, Dattatray J. (RSC Advances, 2015)
WSe2 micro/nanorods were synthesized using one step microwave and hydrothermal methods. The as synthesized micro/nanorod samples of WSe2 were characterized using various characterization techniques such as SEM, TEM, Raman spectroscopy, X-ray diffraction, UV-visible and PL spectroscopy. The as synthesized samples were also tested for their applicability to use as cathode materials for supercapacitor applications. The WSe2 samples prepared by the microwave and hydrothermal methods (with use of tungstic acid as precursor) show noteworthy performance towards supercapacitor application. Our work opens a new avenue to use these simple methods to prepare various morphologies of inorganic nanomaterials and utilize them for various energy and nanoelectronics applications.